PENGEMBANGAN MODUL BERBASIS E-BOOK INTERAKTIF PADA MATA PELAJARAN DASAR DESAIN GRAFIS - Yenzi Rafli; Muhammad Adri (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
Development of interactive e-book based modules as one of the learning media in an effort to convey knowledge information to students in schools to achieve learning objectives. The number of constraints that are present when the learning process takes place such as the absence of students in schools with various kinds of reasons and the absence of teachers when the learning process in the classroom becomes a problem in school education. Learning media is one solution so that students can learn more actively and independently in order to catch up with lessons. The purpose of the development of this interactive e-book based module is to create an interactive e-book based learning media application on the basic subjects of multimedia x-class graphic design designed using Professional PageFlip 3D applications and several other supporting applications. The structure of the material in this e-book uses the Exploratory method. The tutorial and creation of this interactive e-book uses the development model of the IDI (Instructional Development Institute). The result of making this interactive e-book is a learning media application that contains material and video tutorials on basic graphic design lessons. This e-book application has been tested for feasibility by 2 media expert examiners and 2 material expert examiners which obtained results in the aspect of content with a valid level, the average value obtained was 0.95 so that it was declared suitable for use as a learning medium. Keywords : Interactive e-book, learning media, basic subjects of graphic design